EFEITOS DA ÁGUA SUPERFICIAL DE CÓRREGOS DO RIO IVINHEMA-MS EM TESTE COM ALLIUM CEPA - Silva, Elicléia; Meira, Vandressa; Do Amaral, Bruno; Veiga, Luiza; Finoto, Lucilene; Súarez, Yzél (ANAIS DO ENIC, 2018)
-